Review of "The Ghostwriters: Lawyers and the politics behind the judicial construction of Europe" by Tommaso Pavone - William Phelan (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2023)
A review and critique of Tommaso Pavone's recent book 'The Ghostwriters: Lawyers and the Politics behind the Judicial Construction of Europe' (Cambridge University Press, 2022).
Keywords: 330; European Court of Justice; European Law; Legal History